2019
DOI: 10.1111/nmo.13619
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression in irritable bowel syndrome: Exploring the interaction with other symptoms and pathophysiology using multivariate analyses

Abstract: Background Anxiety or depression, in other words, psychological distress, are common comorbidities in patients with irritable bowel syndrome (IBS), but their interaction with pathophysiological factors and other symptoms are unclear. Methods Patients with IBS (Rome III criteria), thoroughly characterized regarding pathophysiology (colonic transit time, visceral sensitivity, and autonomic nervous system [ANS] function), symptom profile (IBS severity, somatic symptoms, gastrointestinal [GI]‐specific anxiety and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 65 publications
2
73
1
2
Order By: Relevance
“…However, most started inappropriately interpret the term “functional” as idiopathic or cryptogenic; unfortunately, the patients suffering from this illness were labeled as neurotic, apprehensive, otherwise healthy individuals with an imaginary illness 3 . The psychogenic origin of the condition is largely based on the uncontrolled or case–control studies that showed that the patients with IBS, particularly those with severe symptoms often have more psychological and psychiatric comorbidities and on the fact that these patients also respond to treatment with psychotropic agents though some studies did show IBS including postinfection IBS (PI‐IBS) to develop more often among patients with anxiety and depression 7–9 . However, IBS is a multifactorial condition, and the existing evidences are not enough to incriminate psychological comorbidity to be uniformly the cause for all patients with IBS.…”
Section: Introductionmentioning
confidence: 99%
“…However, most started inappropriately interpret the term “functional” as idiopathic or cryptogenic; unfortunately, the patients suffering from this illness were labeled as neurotic, apprehensive, otherwise healthy individuals with an imaginary illness 3 . The psychogenic origin of the condition is largely based on the uncontrolled or case–control studies that showed that the patients with IBS, particularly those with severe symptoms often have more psychological and psychiatric comorbidities and on the fact that these patients also respond to treatment with psychotropic agents though some studies did show IBS including postinfection IBS (PI‐IBS) to develop more often among patients with anxiety and depression 7–9 . However, IBS is a multifactorial condition, and the existing evidences are not enough to incriminate psychological comorbidity to be uniformly the cause for all patients with IBS.…”
Section: Introductionmentioning
confidence: 99%
“…IBS is associated with high rates of anxiety and depression in adults which may be associated with visceral hyperalgesia and autonomic nervous system dysfunction 26 . In children with IBS, anxiety and depression correlate with abdominal pain severity 27 .…”
mentioning
confidence: 99%
“…The other two subtypes IBS-M and IBS-D were excluded. Previous study involving 769 IBS patients, demonstrated 25.7% individuals with psychological distress symptom had severe physical manifestation (GI and non-GI symptoms) and lower quality of life than without psychological symptoms ( Cho et al, 2011 ; Midenfjord et al, 2019 ). However, this was not always true.…”
Section: Discussionmentioning
confidence: 94%
“…The symptoms include significant weight change or change of appetite, sleep disturbance, abnormal physical movements such as agitation or retardation, feeling fatigue and difficulty to concentrate (First, 2013). Approximately 25.7% of IBS patients were reported to have borderline and clinical significant depression based on the Hospital Anxiety and Depression Scale score (Midenfjord et al, 2019). Using the same tool, the percentage was a bit more (38.6%) between Korean patients with IBS compared to healthy controls.…”
Section: Introductionmentioning
confidence: 99%